THERMAL AND VELOCITY SLIP EFFECTS ON HEAT AND MASS TRANSFER OF A HYDROMAGNETIC MAXWELL FLUID FLOW OVER A STRETCHING SHEET - Baoku, Ismail; Onifade, Y. S. (FUDMA Journal of Sciences, 2023)
In the present study, the effects of thermal and velocity slip on steady boundary layer magnetohydrodynamic flow, heat and mass transfer of an incompressible upper convected Maxwell fluid over a permeable stretching sheet are analyzed. Similarity transformation technique is adopted to obtain the self-similar coupled nonlinear ordinary differential equations and then the self-similar equations are solved numerically using Runge-Kutta-Fehlberg integration technique with shooting method. The velocity and temperature fields are enhanced by increasing values of velocity and thermal slip parameters respectively. The wall shear stress, rates of heat and mass transfer are enhanced by the increments in the values of thermal and velocity slip parameters. The presence of thermal and velocity slip on the flow fields is found to be of great significance to the investigation.